Design Portable Solar Panel Dan Pengujian Kapasitas Listrik Yang Diterima Terhadap Kemiringan Dan Arah Rotasi Matahari - Karim, Rahmat Abdul; Rais, Sandi; Tjiroso, Bambang (Patria Artha Technological Journal, 2022)
This research aims to create a polycrystalline type solar panel design with a capacity of 100 Wp which is portable (foldable and easy to carry everywhere) and can rotate following the direction of the sun. Solar panels designed are made of Hollow Cm Iron, 1.2 mm Plate Iron, 1.2 mm-2 Inch Stainless Pipe where for solar panel support poles designed with a model can be folded and can rotate 360 degrees so that it can follow the direction of sunlight radiation. The support pole can also be slid up and down where there are 2 scrups that can withstand the shift up and down the support pole.As for the solar panel holder, the design is made by installing hinges and bolts so that the solar panels can be folded and can be tilted following the direction of the sun's rotation. The results of the three-day test in a row from 09-00 to 16-00 WIT, the highest electrical capacity generated by solar panels is between 11:00 – 14:00 WIT on average —an average of 20 V with a solar controller charger output voltage of 19.9 V. The angle of inclination of the solar panel and the direction of the sun rotates following the direction of the sun's rotation